Challenges of acute ischemic stroke treatment in orally anticoagulated patients via telemedicine - Kühne Escolà, Jordi; Nagel, Simon; Panitz, Verena; Reiff, Tilman; Gutschalk, Alexander; Gumbinger, Christoph; Purrucker, Jan (Journal of Clinical Medicine, 2021)
Background: Managing acute ischemic stroke (AIS) in patients receiving treatment with vitamin K antagonists (VKA) or non-VKA oral anticoagulants (NOACs) is difficult and the challenge this poses for stroke telemedicine remains unexplored. Methods: We analyzed data from a random sample (n = 1500) of all teleneurological consultations conducted between July 2015 and December 2017. Management of patients suffering AIS with and without prior oral anticoagulation treatment was characterized, including potential vs. actual treatment with intravenous thrombolysis (IVT) and reasons for withholding it. Results: n = 359 patients had suffered an AIS, of whom 63 (17.5%) were under treatment with oral anticoagulants (VKA, n = 24; NOAC, n = 39). Administration of IVT was more common in patients who had not received prior oral anticoagulation treatment (20.3% vs. 3.2%, p < 0.001). NOAC intake was the primary reason for withholding IVT in 37% of orally anticoagulated patients who were found potentially eligible for IVT. Furthermore, patients under oral anticoagulation tended to be transported to the comprehensive stroke center more often (23.8% vs. 13.9%, p = 0.056). Conclusions: AIS in patients on oral anticoagulation treatment is a frequent reason for telestroke consultation, and NOAC intake constitutes an important barrier to administering IVT.